Facile preparation and characterizations of potential low-cost nanostructured materials for energy gas storage - Misran H.; Aminuddin A.M.; Zini F.A.M.; Ramesh S. (Electrochemical Society Inc., 2023)
Mesoporous ?-alumina with relatively high surface area of 400 m 2/g and pore size of ca. 3.8 nm were successfully prepared using facile and cost-effective method employing sol-gel route at room temperature and atmospheric pressure in the presence of conventional surfactant and fatty alcohol (palm oil derived) as template. The limited amount of water gradually added during the synthesis was found to control the rapid hydrolysis rate of the alumina precursors resulting in mesoporous formation. The mesoporosity were retained when changing the surfactant to fatty alcohol. In addition, the materials porosity was made up from framework porosity as well as textural porosity given rise from the aggregations of ?-alumina nanoparticulates. The Electrochemical Society.